2018
DOI: 10.1103/physrevlett.120.030403
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Open Quantum Systems with Hamiltonian Ensembles and the Nonclassicality of the Dynamics

Abstract: The incoherent dynamical properties of open quantum systems are generically attributed to an ongoing correlation between the system and its environment. Here, we propose a novel way to assess the nature of these system-environment correlations by examining the system dynamics alone. Our approach is based on the possibility or impossibility to simulate open-system dynamics with Hamiltonian ensembles. As we show, such (im)possibility to simulate is closely linked to the system-environment correlations. We thus d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
88
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 29 publications
(51 reference statements)
1
88
0
Order By: Relevance
“…Averaged dynamics of Hamiltonian ensembles. A HE {(p λ , H λ )} λ is a collection of Hermitian operators H λ acting on the same system [17,39], where each member Hamiltonian is drawn according to the probability distribution p λ ≥ 0. A system ρ 0 , isolated from any environment, is sent into a unitarily-evolving channel ρ λ (t) = U λ ρ 0 U † λ , with U λ = exp[−i H λ t/ ] for a chosen H λ according to p λ .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Averaged dynamics of Hamiltonian ensembles. A HE {(p λ , H λ )} λ is a collection of Hermitian operators H λ acting on the same system [17,39], where each member Hamiltonian is drawn according to the probability distribution p λ ≥ 0. A system ρ 0 , isolated from any environment, is sent into a unitarily-evolving channel ρ λ (t) = U λ ρ 0 U † λ , with U λ = exp[−i H λ t/ ] for a chosen H λ according to p λ .…”
Section: Resultsmentioning
confidence: 99%
“…An autonomous system-environment arrangement is characterized by a time-independent total Hamiltonian H T and evolves unitarily with U T = exp[−i H T t]. We have shown that [17], if the total system ρ T (t) = U T ρ T (0) U † T remains at all times classically correlated between the system and its environment, displaying neither quantum discord [43,44] nor entanglement, then the reduced system dynamics ρ S (t) = E t {ρ S (0)} = Tr E [ρ T (t)] can be described by a time-independent HE equipped with a legitimate (i.e., non-negative and normalized to unity) probability distribution. Moreover, such ensemble description under classical environments in the absence of back-action has also been discussed in the literature [45][46][47].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our formulation is closest to the one in [5]; in the case of maximal dephasing, it leads to the concept of a stable basis that recovers the "pointer basis" introduced by Zurek [8] and also embodies the simplest informationpreserving structure [9]. For more recent representative contributions on decoherence through random unitary models see for instance [10,11,12,13].…”
Section: Introductionmentioning
confidence: 96%